Molecular characterization of potent antibacterial compound 4-(3-methylazetidin-1-yl)pentan-2-ol from Calophyllum inophyllum seed oil. (January 2023) - Anjukam, Elamaran; Ramesh, Manickam; Rajalakshmi, Arumugam; Kavitha, Kuppuswamy; Prakash, Mani; Suresh, Gopal; Puvanakrishnan, Rengarajulu; Ramesh, Balasubramanian
Abstract: Calophyllum inophyllum (Calophyllaceae) has wide applications in traditional folk medicine. The methanol extract of C . inophyllum exhibited good antibacterial activities (17 ± 1.73 to 24 ± 1.15 mm) against Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa. The bioactive constituents of this seed oil were purified by thin-layer chromatography (TLC) and column chromatography and characterized by gas chromatography-mass spectrometry (GC-MS). The compounds such as Benzene, 1-bromo-4- (1, 3-dichloropropyl), furan −2 –carboxaldehyde 5 – (3-nitrophenoxy) and (4 – iodopyrazol-1-yl) acetonitrile were predominant (28.14%) followed by 2-ethylacridine, 2-methyl-7-phenylindole, 5-methyl-2-phenylindolizine (9.18%) and then by E−11-hexadecenal, Cis -9-hexadecenal and 9, 17-octadecadienal (z) (8.90%). Further, preparative high performance liquid chromatography (HPLC) and spectroscopic studies such as Fourier-transform infrared spectroscopy (FTIR) and Nuclear magnetic resonance (NMR) combined with CSEARCH spectral similarity search demonstrated that the bioactive antibacterial compound in the active fraction is 4- (3-methylazetidin-1-yl) pentan-2-ol. Graphical abstract: Image 1 Highlights: Solvent extraction of Calophyllum inophyllum seeds. Assessment of antibacterial activity of the extract. Purification of bioactive compounds by TLC, column chromatography, and (GC-MS). Characterization by FTIR and NMR. Identification of the novel antibacterial compound.